A Brief Analysis of Chinese Hieroglyphs in the Zero-based Teaching of Chinese Characters as a Foreign Language - JIN, YING (Chinese Language and Culture Journal, 2021)
Abstract With the increasing international status of China, the ever-developing political, economic and trade relations between China and the world have caused more and more foreigners to learn Chinese, however, because Chinese characters are different from syllable texts, they are ideograms but not phonography, the learning of Chinese characters for beginners is very difficult and a bit boring. The purpose of this article is to enable students to understand the structure and meaning of Chinese characters in an intuitive way at the early stage of learning Chinese characters by showing the process of formation and evolution of Chinese hieroglyphs and Chinese characters to students through the animated pictograph display. And then to connect the learned hieroglyphs into a story to students to strengthen the memory of them, to better learn and master Chinese characters. This article uses literature method, historical research method, etc. to obtain relevant information, sort out and study how to introduce Chinese hieroglyphs into zero-based Chinese character teaching. Through the pictographic teaching of visual representation, it strengthens learners’ impression of Chinese characters and arouses their interest in learning Chinese characters. It also recommends to use multimedia technology, visual representation and graphic teaching methods to help zero-based learners to learn Chinese characters quickly and efficiently. Key words：Chinese hieroglyphs; Visual representation; Zero-based learners; Learning Chinese characters